Detection of the cyanomidyl radical (HNCN): a new interstellar species with the NCN backbone. Issue 1 (2nd July 2021) - Rivilla, V M; Jiménez-Serra, I; García de la Concepción, J; Martín-Pintado, J; Colzi, L; Rodríguez-Almeida, L F; Tercero, B; Rico-Villas, F; Zeng, S; Martín, S; Requena-Torres, M A; de Vicente, P
ABSTRACT: We report here the first detection in the interstellar medium of the cyanomidyl radical (HNCN). Using the Yebes 40m and the IRAM 30m telescopes, we have targeted the doublets of the N  = 2–1, 4–3, 5–4, 6–5, and 7–6 transitions of HNCN towards the molecular cloud G+0.693-0.027. We have detected three unblended lines of HNCN, these are the N  = 6–5 doublet and one line of the N  = 4–3 transition. Additionally, we present one line of the N  = 5–4 transition partially blended with emission from other species. The local thermodynamic equilibrium best fit to the data gives a molecular abundance of (0.91 ± 0.05) × 10 −10 with respect to H2 . The relatively low abundance of this species in G+0.693-0.027 and its high reactivity suggest that HNCN is possibly produced by gas-phase chemistry. Our work shows that this highly reactive molecule is present in interstellar space, and thus it represents a plausible precursor of larger prebiotic molecules with the nitrogen–carbon–nitrogen backbone such as cyanamide (NH2 CN), carbodiimide (HNCNH), and formamidine (NH2 CHNH).